A Comprehensive Analysis of Genomics and Metagenomics in a Heterozygote Familial Hypercholesterolemia Family - Liu, Honghong; Jin, Ye; Tian, Ran; Feng, Siqin; Zhang, Shuyang; Zhang, Chenhong (Frontiers in Cellular and Infection Microbiology, 2021)
Familial hypercholesterolemia (FH) is an inherited rare disease leading to markedly elevated low-density lipoprotein cholesterol (LDL-C) levels and increased risk for cardiovascular event. Gut microbiota has been implicated as a pivotal contributing factor in hyperlipidemia, however, its role in FH remains elusive. We performed whole-exome and metagenomics sequencing on a family with 22 members in which myocardial infarctions occurred at a young age with unclear etiology. We confirmed the missense mutation of LDLR c.1723C>T accounted for the abnormal cholesterol metabolism in the family through co-segregation analysis. In addition, Prevotella dentalis was found elevated and strongly associated with LDL-C level in FH family members with mutation of LDLR c.1723C>T compared to unaffected members with hyperlipidemia. Overall, our work suggests that whole-exome sequencing can facilitate identification of disease-causing variants and enable preventive treatment of FH. Our metagenomics analysis provides early insights into potential contributions of host–microbe interactions in genetic and common hypercholesterolemia.